CONDITIONS FOR TRANSITION FROM BARRIER TO POROUS OXIDATION OF ALUMINUM IN PHOSPHORIC ACID SOLUTIONS. (1st December 2015) - Mirzoev, R.A.; Davydov, A.D.; Kurmyalevskaya, D.K.; Bazylyk, A.N.; Vystupov, S.I.
ABSTRACT: Anodic oxidation of aluminum foil specimens in the phosphoric acid solutions of various concentrations was studied under the galvanostatic conditions at various current densities. The efficiency of barrier oxidation was determined by the slopes of linear portions of time dependence of voltage across the electrochemical cell electrodes. The SEM micrographs of oxidized specimens are presented. It was shown that the critical oxidation efficiency for the transition from the barrier oxidation to porous oxidation is equal to the reciprocal of the Pilling–Bedworth ratio (0.61). The power dependence of the rate of field assisted ejection of metal cations from oxide film on the current density was supported experimentally. The exponent of power function was found to be about 0.5.